A probabilistic approach in scheduling spinning reserve based on forced outage rate of generating units and value of loss of load - Pagobo, Gerald R.
Efficient techniques of determining Spinning Reserve requirements have been studied and implemented by various transmission system operators worldwide. These techniques vary in approach but all essentially recognize the significance of generating unit failure probability in the evaluation. The current reserve scheduling methodology used in the Philippines, however, described in TransCo's Ancillary Service Procurement Plan, is based on the notion that the level of the spinning reserve provided should be equal to the largest online load, so that in the event that the generating unit serving this load fails, loss of load would not occur. The deterministic approach though seemingly logical, ends up in a higher-than-required reserve scheduled and fails to consider both generating unit reliability and the willingness of the consumers to acquire or pay for the reserve. This study presents a probabilistic methodology based on the generating unit random failures and the value that consumers place on the loss of load. The end result is a cost-benefit optimized spinning reserve.